Ethnic minority community access to popular culture in the context of tourism: (case of Thai ethnic group in Lac Village, Mai Chau, Hoa Binh, Vietnam) - Nam, Nguyen Thanh (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
Tourism is a growing service economic sector that creates jobs for many communities in the world. Ethnic minority communities in many countries are also now taking part in tourism activities. Vietnam is a country with great potentials for natural landscapes, historical values, indigenous culture of ethnic groups with habits and lifestyles, rich culinary culture of regions. It is the basis for development of tourism.
Keywords: ethnic minority community; popular culture; tourism